ISLAMIC CREDIT CARD PRODUCT DEVELOPMENT STRATEGY (CASE STUDY OF SHARIA BANKS IN INDONESIA) - Rafika Rahmawati; Agung Dharmawan Buchdadi; Adam Zakaria (International Conference on Humanity Education and Society (ICHES), 2026)
This research will map the internal and external factors that influence the development of Islamic Credit Card products in Indonesia and analyze the appropriate alternative strategies for the development of these products. The analysis was carried out, namely Internal Factors Evaluation (IFE) and External Factors Evaluation (EFE) matrix analysis, Internal and External (IE) matrix analysis, and SWOT analysis to determine strategic alternatives. The results of the IFE and EFE assessments identified that the development of Islamic credit cards in Indonesia is in quadrant IV, namely "Grow and Develop". Meanwhile, based on the strategic quadrant, the development of Islamic Credit Cards is in the IA quadrant, namely Rapid Growth, which shows development in good condition and is supported by the internal and external environment. Based on these conditions, an alternative strategy for developing a Sharia Credit Card product that can be done is the S-O strategy. The S-O strategy is based on the results of a SWOT analysis, including encouraging other Islamic banks to issue Islamic Credit Card products and synergize with many e-commerce sites to expand the reach of the community